Pengaruh Kualitas Produk, Citra Merek , dan Persepsi Harga terhadap Keputusan Pembelian Produk Skincare Ms. Glow (Studi Kasus pada konsumen produk Skincare MS. GLOW di Kota Semarang) - Vika Puji Astutik; Bambang Sutedjo (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine product quality, brand image and price perception on the purchase decision of MS skincare products. GLOW in the Semarang area. The population in this study are consumers who will buy MS products. GLOW in the Semarang area. The sampling technique used by the researcher is purposive sampling technique, by distributing questionnaires to users who have used MS products. GLOW in the Semarang area. The criteria used as samples for this study are male and female, at least 17-50 years old and have made a purchase at least 1 time on MS products. GLOW in the Semarang area. The sampling technique used is based on Roscoe's (1975) theory, the researchers set a minimum number of samples in this study of 92 respondents obtained from the number of variables x the number of indicators. Simultaneous test results using the F test indicate that the multiple linear regression model is feasible as a research model. Furthermore, using the t test shows that product quality, brand image and price perception have a significant and positive effect on purchasing decisions.